Mental health training and education in South America: SUD World Project. Issue 2 (May 2014) - Symeon, Christopher; Pritchard, Dewi; Aguirre, Lucienne; Jimenez, David
Abstract : There is a clear interest in many countries in improving education, training and academic opportunities in mental health. The goal of SUD World Project is to create links between South America and Europe that will actively enhance education and training in mental health.